Biotechnological potential of Clostridium butyricum bacteria - Szymanowska-Powałowska,Daria (2014)
In response to demand from industry for microorganisms with auspicious biotechnological potential, a worldwide interest has developed in bacteria and fungi isolation. Microorganisms of interesting metabolic properties include non-pathogenic bacteria of the genus Clostridium, particularly C. acetobutylicum, C. butyricum and C. pasteurianum. A well-known property of C. butyricum is their ability to produce butyric acid, as well as effectively convert glycerol to 1,3-propanediol (38.2 g/L). A conversion rate of 0.66 mol 1,3-propanediol/mol of glycerol has been obtained. Results of the studies described in the present paper broaden our knowledge of characteristic features of C. butyricum specific isolates in terms of their phylogenetic affiliation, fermentation capacity and antibacterial properties.